STUDY OF THE IMPACT OF THE USE OF DIGITAL DEVICES IN CLASSROOM TEACHING IN MIDDLE LEVEL SCHOOLS ON STUDENT ATTENDANCE AND ACADEMIC ACHIEVEMENT - Diksha; Gola, Rajkumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Any person's all-round development takes place only through education, he develops the society and the country by becoming a useful member of the society. Primary education is the foundation stone for making a child civilized and cultured. Without strengthening it, the desired society cannot be achieved. Therefore, there is always a pressure on the leaders of the society and the country, as to how to organize this level of education so that the desired results can be achieved and the nursery being prepared for the needs of the society and the country can be given the right direction so that they can become capable members of the society and the country and contribute significantly to the upliftment of the country and human society. For all this, it is necessary that such arrangements should be made according to the changing times so that they are ready to receive education, they receive education with entertainment and they feel good in coming to and staying in school. This can happen only when the things prevalent in the society are available in the school so that the environment there does not seem different to them which is boring from their lifestyle. Rousseau says, 'We cannot learn anything from a student whom we hate.' Children should not only come to school but also stay there regularly till school hours and happily absorb the information given on various subjects in a better way. Various commissions have from time to time emphasized on increasing the stay of children in school. Various efforts have been made for all this. To make teaching interesting and understandable, emphasis has been laid on the use of audio, visual and audio-visual resources in this field.